Children Who Experience Unintentional Injuries: Their Functional Profiles. (3rd November 2022) - Rosenblum, Sara; Nardi-Moses, Tal; Goez, Helly; Demeter, Naor
Abstract : Unintentional injuries are accidents that pose a major health problem among school children. This study compared the functional behavior and executive function characteristics of school-aged children who experienced unintentional injuries with those of controls who had not been injured. We investigated the background characteristics of injured children, injury characteristics, and parents' perceptions of the children's functional behaviors and executive function abilities. The study included 53 children aged 6 years to 18 years. Of them, 32 had experienced unintentional injuries. The 21 children who had not experienced unintentional injuries served as a control group matched for age and living environment. Parents of both groups completed (1) a demographic questionnaire addressing their children's background, daily functional behavior characteristics, and injury characteristics and (2) the Behavior Rating Inventory of Executive Function (BRIEF). Sixty percent of the children in the research (injured) group had been prediagnosed with learning disabilities or attention deficit hyperactivity disorders, compared with no child in the control (uninjured) group. Most injuries were limb fractures (60%) and sustained outside the home (50%). Parents of children who had been injured expressed significantly more concerns about their children's daily behavior than did parents of the control group and reported their children as usually, but not always, independent and responsible. Compared with the children in the uninjured group, the children in the injured group had significantly lower executive function abilities in the BRIEF's eight subscales, total behavioral regulation and metacognitive indices, and global executive function scores (p < .001 ). Children with certain diagnoses, functional behavior features, and deficient executive function abilities may be at risk for unintentional injuries. Raising occupational therapists' awareness of these aspects may contribute to identifying, treating, and preventing accidental injuries among at-risk children.